1993
DOI: 10.1111/j.1471-4159.1993.tb07465.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of mRNAs Encoding Rat Brain Kainate/AMPA Receptors: A Northern Analysis Study

Abstract: Functionally diverse kainate/alpha-amino-3-hydroxy-5-methyl-4- isoxazolepropionic acid (AMPA) receptors are generated by assembly of glutamate receptor (GluR)1, 2, and 3 subunits into homomeric and heteromeric channels. We examined GluR1, 2, and 3 gene expression in embryonic, neonatal, and adult rat brain by northern analysis under conditions of high stringency. In the adult, hybridization to a GluR1 riboprobe revealed the presence of an abundant RNA species, 5.2 kb in size, and minor bands of 3.2 and 3.9 kb.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 32 publications
10
44
0
3
Order By: Relevance
“…Expression of all AMPA receptor subunits in the forebrain was detectable at 24 hpf and followed a progressive maturational enrichment. The same pattern of AMPA receptors in the forebrain during development was also observed in other vertebrate systems such as rat and ferret (Durand and Zukin, 1993;Snyder-Keller and Costantini, 1996;Martin et al, 1998;Smith and Thompson, 1999). Furthermore, high levels of glutamate are found in the zebrafish olfactory bulb in the dorsal telencephalon, from 24 hpf onward (Sakata et al, 2003).…”
Section: Discussionmentioning
confidence: 50%
“…Expression of all AMPA receptor subunits in the forebrain was detectable at 24 hpf and followed a progressive maturational enrichment. The same pattern of AMPA receptors in the forebrain during development was also observed in other vertebrate systems such as rat and ferret (Durand and Zukin, 1993;Snyder-Keller and Costantini, 1996;Martin et al, 1998;Smith and Thompson, 1999). Furthermore, high levels of glutamate are found in the zebrafish olfactory bulb in the dorsal telencephalon, from 24 hpf onward (Sakata et al, 2003).…”
Section: Discussionmentioning
confidence: 50%
“…These results suggest that the native AMPA receptors of Meynert neurones form a mosaic of several subunits which change at various developmental stages while the ratio of Ca¥-permeable GluR-1,3,4 subunits to that of the Ca¥-impermeable GluR-2 subunit may decline gradually during the developmental stages. In fact, the ratio of GluR-1 and GluR-3 to GluR-2 gene expression in the rat brain at various stages of development determined by an in situ hybridization study was high in postnatal CNS neurones but declined monotonically with age (Durand & Zukin, 1993). In the present study, we found that the Meynert neurones became less responsive to NMDA with age, while the KA and AMPA responses gradually increased.…”
Section: Kaïampa Responsesupporting
confidence: 49%
“…This is in line with the identification of AMPARs at early embryonic stages (E14-15) in other rat brain regions including hypothalamic neurons [12] and raphe cells [13]. AMPA and NMDA receptor mRNAs have also been detected in CA1 early in development by in situ hybridization [14] and Northern analysis [15]. Glutamatergic synaptic transmission in the mammalian brain can be detected electrophysiologically at late prenatal stages and early in postnatal development -for example, in neocortex [16,17,18] and hippocampus [19,20].…”
Section: Glutamate Transmission and Silent Synapses Early In Developmentsupporting
confidence: 48%